PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT (LPM) DALAM MENINGKATKAN KESEJAHTERAAN DI DESA KARYA INDAH KECAMATAN TAPUNG - Ikhsan Mardi Arjuna; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research examines the role of Community Empowerment Institutions in improving welfare in Karya Indah village, Tapung sub-district, Kampar district. Community Empowerment Institution (LPM) is one vehicle for community participation formed with the aim of empowering the community in a village which in this case is focused on the economy. The program from (LPM) itself which is related to empowering the community in the economic sector is a waste bank and also sewing. The research method used is descriptive quantitative method, the authors conducted a questionnaire to obtain data on the role of community empowerment institutions (LPM) in improving welfare in the village of indah indah tapung sub-district Kampar district with a sample of 62 people with a sampling technique that is simple random sampling. The results of this study indicate that the Community Empowerment Institution has formed two programs to improve the community's economy, namely garbage banks and sewing, and currently (LPM) Desa Karya Indah has not been able to provide its role to the maximum, which is seen as no increase in the economy or the provision of income for the affected villages. share existing aspects. Keyword : Community Empowerment Institutions, Program, Role